KESENJANGAN NILAI SUMATIF DAN PERILAKU KEAGAMAAN SISWA DALAM PEMBELAJARAN PAI: ANALISIS TAKSONOMI MARZANO DI SDIT IZZATUL ISLAM MUARO JAMBI - Irawan, Dedy; Latif, Maskuri; Sari, Fiqi Nurmanda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic Religious Education (PAI) is expected not only to develop students’ religious knowledge but also to foster religious behavior and internalization of Islamic values. However, assessment practices in PAI learning remain predominantly focused on cognitive-based summative evaluation. This study aims to analyze the gap between students’ summative assessment scores and their religious behavior from the perspective of Marzano’s Taxonomy. Employing a qualitative descriptive approach, the study involved fourth-, fifth-, and sixth-grade students at SDIT Izzatul Islam Muaro Jambi. Data were collected through documentation of summative scores, observation of religious behavior, and supporting interviews. The findings reveal that although most students achieved high academic performance in PAI, their consistency in religious behavior and intrinsic religious awareness was not yet optimal. From Marzano’s Taxonomy perspective, this condition indicates achievement in the knowledge acquisition dimension, but limited development in meaningful knowledge utilization and the self-system dimension. The study emphasizes the need to reorient PAI learning and assessment toward a more holistic and reflective approach to achieve authentic and sustainable religious character development. Keywords: Islamic Religious Education, Summative Assessment, Religious Behavior, Marzano’s Taxonomy